Analisis Wacana Kritis Pada Media Massa Daring (Online) Bantennews.co.id Kolom Hukum Edisi Februari 2021 - Asep Yana Yusyama; Ratna Khoirunnisa (Universitas Batanghari Jambi, 2021)
News in the mass media column has changed the paradigm of society since long time ago. As the times progress, the mass media are also increasingly progressive and dynamic in reporting. Currently, there are many news media in the form of online which is indeed a relatively fast reporting process compared to conventional mass media, especially when examined from a critical discourse point of view. The research question is